PERCEIVED STRESS AND ADEQUACY OF SOCIAL SUPPORT: IMPLICATIONS FOR SUUBJECTIVE WELL-BEING IN MARRIED DOCTORS - Ilyas, Uzma; Fatima, Arooj; Hashmi, Aatka; Rashid, Rabbia (Pakistan Armed Forces Medical Journal, 2020)
Objective: To investigate how stress, social support and subjective happiness effect the lives of married doctors.Study Design: Correlational study.Place and Duration of Study: Different government hospitals over 4 months, from Oct 2016 to Jan 2017.Methodology: For the current study n=200 doctors were included through purposive sampling. All those doctors who were married for more than two years and practicing full time in hospital were included. Structured questionnaires of Perceived Stress Scale, Multidimensional Perceived Social Support and Subjective Happiness Scale were administered on the participants. Attributing factors like age, gender, work experience, number of working hours were noted.Results: Predictive effect of perceived stress and social support on subjective happiness was assessed by Hierarchical regression for both male and female doctors which showed unstandardized beta (β) as 0.31 in male doctors and 0.53 in female doctors with 95% confidence interval and p-value of 0.001. Social support, subscale family support and perceived stress were negatively correlated (r=-0.23, p